Effect of iridium oxide as an additive on catalysts with different Pt contents in cell reversal conditions of polymer electrolyte membrane fuel cells. (8th January 2022) - Ahn, Chi-Yeong; Kim, Sungjun; Choi, Hyuck Jae; Lee, Jongmin; Kang, Sun Young; Kim, Ok-Hee; Shim, Hyungwon; Kim, Young-Shik; Sung, Yung-Eun; Kwon, Oh Joong; Cho, Yong-Hun
Abstract: Cell reversal is observed when a current load is applied to the polymer electrolyte membrane fuel cell under fuel starvation conditions. Cell reversal causes severe corrosion (or oxidation) of the carbon support in the anode, which leads to a decrease in overall fuel cell performance. To suppress the corrosion reaction of carbon under cell reversal conditions and to increase the durability of fuel cells, studies on anode additives are being conducted. However, studies on the effect of additives on catalysts with different platinum contents have not been conducted. In this study, 20 wt%, 40 wt%, 60 wt% commercial Pt/C catalyst was applied to the anode, and 50 cycles of cell reversal were performed. Furthermore, the performance change with and without IrO2 as an additive was observed and its effect was assessed. Changes in the morphologies of the electrodes before and after cell reversal tests were also observed using a transmission electron microscope and a scanning electron microscope. The higher the platinum content of the catalyst, the more resistant to cell reversal. In addition, the addition of IrO2 to the anode effectively prevents performance degradation due to cell reversal. Highlights: Catalysts with different Pt loadings were applied to the anode of the fuel cell. Effect of additives such as IrO2 in the fuel starvation environment was investigated. Electrochemical performance and CR tests were performed. Added IrO2 to fuel cell anode clearly prevented electrode degradation. Findings can be used for electrode preparation with different Pt contents.